IJTIMOIY HAYOTDA MA’NAVIY- ESTETIK TARBIYA - Abdimuratova, N.P. (SCIENCE and SOCIETY, 2024)
The main subject of the article is providing solidity of a family, to value a person, his virtue and prolongation of his generation, being devoted to our ancestor’s directions and to perfect our generation in being clever and happy is our main aim.
Keywords: psychology; esthetics; family; education; harmonically; developed generation; ancestors